Rethinking Gender Inequalities in Organizations - Dick, Penny (Edward Elgar Publishing, 2024)
In this thoughtful book, Penny Dick challenges orthodox views of gender inequality. Combining post-structuralist thinking with process ontology, the author presents a novel conceptual approach to rethinking gender inequalities in organizations and management settings.